Potential Production of Polyunsaturated Fatty Acids from Microalgae - Noer Abyor Handayani; Dessy Ariyanti; Hady Hadiyanto (Chemical Engineering Diponegoro University, 2011)
Currently, public awareness of healthcare importance increase. Polyunsaturated fatty acid is an essential nutrition for us, such arachidonic acid, docosahexaenoic acid and eicosapentaenoic acid. The need of Polyunsaturated fatty acid generally derived from fish oil, but fish oil has a high risk chemical contamination. Microalgae are single cell microorganism, one of Phaeodactylum tricornutum which have relatively high content of eicosapentaenoic acid (29,8%). Biotechnology market of Polyunsaturated fatty acid is very promising for both foods and feeds, because the availability of abundant raw materials and suitable to develop in the tropics. This literature review discusses about the content of Polyunsaturated fatty acid in microalgae, omega-3, omega-6, Polyunsaturated fatty acid production processes, and applications in public health